Evaluation of an oral appliance in patients with mild to moderate obstructive sleep apnea syndrome intolerant to continuous positive airway pressure use: Preliminary results. (June 2016) - Cantore, S; Ballini, A; Farronato, D; Malcangi, G; Dipalma, G; Assandri, F; Garagiola, U; Inchingolo, F; De Vito, D; Cirulli, N
Obstructive sleep apnea syndrome (OSAS) is a phenomenon of repeated, episodic reduction, or cessation of airflow (hypopnea/apnea) as a result of upper airways obstruction. First-line treatment in younger children is adenotonsillectomy, although other available treatment options in middle-aged adults include continuous positive airways pressure (CPAP) and airway adjuncts. Oral appliances (OA) are a viable treatment alternative in patients with OSAS. The objective of this study was to assess, in a 1-year follow-up study, an OA in OSAS patients. The participants were subjected to polysomnographic examination with a validated device (MicroMESAM). Eight participants were fitted with a Thornton Adjustable Positioner (TAP). The participants were asked to wear the test appliance for 7 nights, and in case of compliance, for 6 months. The selected patients record their usage of the appliance and any adverse effects in a treatment journal. The research focused on the following outcomes: sleep apnea (i.e. reduction in the apnea/hypopnea index) and the effect of oral appliances on daytime function. In conclusion, the results suggest that OA have a definite role in the treatment of snoring and sleep apnea.